Design and reliability analysis of FRP-reinforced concrete columns. (December 2020) - Tarawneh, Ahmad; Majdalaweyh, Sereen
Abstract: ACI 440-15 does not provide design provisions for columns and requires ignoring the compression contribution of FRP bars. However, this paper provides a design recommendation to include FRP bars' compression for more accurate predictions. The compressive contribution is included by limiting the strain to 0.002 for compression bars. This recommendation is valid for circular and rectangle columns subjected to concentric and eccentric loading. This paper supports the design recommendation by reliability analyses using Monte Carlo simulations. The analyses are based on the results of 194 column tests surveyed from literature. The analysis has been conducted for a wide range of live to dead load ratios. Generally, the results show that FRP-reinforced columns exhibit an acceptable levels of reliability index. Additionally, the reliability index was not sensitive to reinforcement ratio, eccentricity level, or concrete strength. However, the results show that CFRP columns have a higher reliability index than GFRP columns. Consequently, a lower strength reduction factor for GFRP bars can be utilized to achieve a consistent safety level.